ANALISIS WACANA NASKAH DRAMA “RUWET” KARYA SUNARDI: ANALISIS WACANA NASKAH DRAMA “RUWET” KARYA SUNARDI - Anastasia Septianggi Sri Hartanti; Ike Anisa Anisa (LPPM Universitas Widya Dharma, 2023)
The Drama Script entitled “Ruwet” by Sunardi, M.Pd was analyzed in the study of grammatical and lexical discourse. Discourse analysis. The grammatical aspect consists of four parts, namely reference, insertion, duplication, and stringing. The lexical aspect is the relationship between the elements contained in the discourse. The lexical aspect consists of six parts, namely repetition, synonym, antonymy, collocation, and hyponymy. Researchers are interested in researching the drama script entitled